2021
DOI: 10.1063/5.0039610
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of van der Waals complexes through three-body recombination

Abstract: In this work, we show that van der Waals molecules X-RG (where RG is the rare gas atom) may be created through direct three-body recombination collisions, i.e., X + RG + RG → X-RG + RG. In particular, the three-body recombination rate at temperatures relevant for buffer gas cell experiments is calculated via a classical trajectory method in hyperspherical coordinates [Pérez-Ríos et al., J. Chem. Phys. 140, 044307 ( 2014)]. As a result, it is found that the formation of van der Waals molecules in buffer gas cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…The present approach is based on a classical trajectory (CT) method in hyperspherical coordinates, which has shown efficiency for reactive collisions of three neutral atoms [11][12][13]29] as well as for ion-neutral-neutral ternary recombination processes [30][31][32]. The method is adapted to the present problem representing the O 2 molecule as a super-atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present approach is based on a classical trajectory (CT) method in hyperspherical coordinates, which has shown efficiency for reactive collisions of three neutral atoms [11][12][13]29] as well as for ion-neutral-neutral ternary recombination processes [30][31][32]. The method is adapted to the present problem representing the O 2 molecule as a super-atom.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 gives the rate coefficients for the formation of all three possible products of the reaction, O 3 , ArO 2 , and ArO. The figure demonstrates two distinct characteristics: First, at low collision energies (E c 130 K) [13,29], ArO 2 is formed more quickly than ArO, which is formed more quickly than O 3 (assuming equal densities of Ar, O, and O 2 ). The result is explained by the fact that the attractive potential of the Ar-O 2 system decays slower than that of Ar-O, so that it has a larger density of available vibrational states to be formed (a larger phasespace volume in the classical formulation of the problem).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37][38] In Ref. [39], we considered the formation of atom-rare gas vdW molecules via a direct three-body recombination mechanism at temperatures relevant for buffer gas cell experiments. As a result, we found that almost any atom a) Electronic mail: mirahmadi@fhi-berlin.mpg.de b) Electronic mail: jperezri@fhi-berlin.mpg.de in a helium buffer gas will evolve into a vdW molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Fueled by those results, our goal in the present work is to present a comprehensive study of A + B + B → AB + B reactions and derive a classical threshold law for the formation of vdW molecules in cold environments. To investigate this problem, we use a classical approach in hyperspherical coordinates, which has previously been used to consider the three-body recombination of three neutral atoms, 33,39,40 as well as ion-neutral-neutral threebody recombination processes. 36,37,41 In order to derive a threshold law, we have obtained an effective long-range potential in hyperspherical coordinates.…”
Section: Introductionmentioning
confidence: 99%